The Job Performance of Philippine National Police Frontliners during the COVID-19 Pandemic - Abragon, Mario; Buena-Villa, Elizabeth; Dalugdog, Wilfredo (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2023)
The COVID-19 pandemic created not only threats to public health but also brought new and extraordinary challenges in the lives of law enforcement agencies worldwide. This study assessed the job performance of the Philippine National Police (PNP) frontliners during the COVID-19 pandemic in the three cities of the province of Cavite, Philippines. The self-made survey questionnaire was distributed conveniently to 384 residents per city. The study revealed that police assistance gained a very effective rating, however, the enforcement of Inter-Agency Task Force (IATF) health protocols was rated only effective, and the PNP reliability during the pandemic was rated very effective. The implication of this study is that during the COVID-19 pandemic, the residents of the said cities still trusted the PNP frontliners even though they rated only effective in the enforcement of IATF health protocols.